If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) + -1(x + -1) * 2 = 7x Reorder the terms: (3 + x) + -1(x + -1) * 2 = 7x Remove parenthesis around (3 + x) 3 + x + -1(x + -1) * 2 = 7x Reorder the terms: 3 + x + -1(-1 + x) * 2 = 7x Reorder the terms for easier multiplication: 3 + x + -1 * 2(-1 + x) = 7x Multiply -1 * 2 3 + x + -2(-1 + x) = 7x 3 + x + (-1 * -2 + x * -2) = 7x 3 + x + (2 + -2x) = 7x Reorder the terms: 3 + 2 + x + -2x = 7x Combine like terms: 3 + 2 = 5 5 + x + -2x = 7x Combine like terms: x + -2x = -1x 5 + -1x = 7x Solving 5 + -1x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 5 + -1x + -7x = 7x + -7x Combine like terms: -1x + -7x = -8x 5 + -8x = 7x + -7x Combine like terms: 7x + -7x = 0 5 + -8x = 0 Add '-5' to each side of the equation. 5 + -5 + -8x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = 0 + -5 -8x = 0 + -5 Combine like terms: 0 + -5 = -5 -8x = -5 Divide each side by '-8'. x = 0.625 Simplifying x = 0.625
| 4x-5=o | | 21y+y=180 | | 6.5a+13=84.5 | | 8g+16=5g-6 | | 5.5x+12=61.5 | | 8m+9=6m-5 | | (0.00623-x)(0.00414-x)= | | 21x+9=23x-3 | | 12x-20=7x+10 | | 59-61x+18x-32=29x+35+43x+79 | | N-24=3(-n+4) | | M-4m=2n | | N-24=(-n+4) | | 28+5x=9x | | 5z^3=-5z | | 4x-3(x-5)+x=-9 | | 6(2x+1)=6(1+7x) | | 4x-3(x-5)+x=9 | | -7(x-2)=-3(x-5) | | 126=-9r | | (0.20+x)(0.12+x)= | | 3r^8=48r^6 | | .1x+.06y=7500 | | -2f+6=4-1(3f-2) | | 6x-4=-80 | | 3-p=3-p | | 11y+17= | | -x^8=2 | | 16s^2-21=0 | | 5t^6=15t^5 | | -13x-21=15 | | z^6+8+8i=0 |